Analysis of dc-Link Voltage Switching Ripple in Three-Phase PWM Inverters - Marija Vujacic; Manel Hammami; Milan Srndovic; Gabriele Grandi (Energies, 2018)
The three-phase voltage source inverter (VSI) is de facto standard in power conversion systems. To realize high power density systems, one of the items to be correctly addressed is the design and selection of the dc-link capacitor in relation to the voltage switching ripple. In this paper, effective formulas for designing the dc-link capacitor as a function of the switching voltage ripple amplitude are obtained, considering the operating conditions such as the modulation index and the output current amplitude. The calculations are obtained considering the requirements and restrictions referring to the high (switching)-frequency dc-link voltage ripple component. Analyses have been performed considering the dc source impedance (non-ideal dc voltage source at the switching frequency) and a balanced load. Analytical expressions are derived for the dc-link voltage switching ripple amplitude and its maximum value over the fundamental period. Different values of modulation index and output phase angle have been considered and different diagrams are presented. Analytical results were validated both by simulations and comprehensive experimental tests.